A Conceptual Model of Game-Based learning with Emphasis on Skill Training: A meta-synthesis - shahrzad saffari; Rezvan Hakim zade; Marzieh Dehghani; Masoud Gholamali lavasani (Shahid Chamran University of Ahvaz, 2021)
IntroductionTeaching and learning in primary school require attention to the physical, cognitive, emotional and social needs of students in this period. In this regard, play is one of the mechanisms that can turn the flow of education and learning in the elementary school, especially in the first period (first, second, third) into an exciting, uplifting, enjoyable and creative process. The present study seeks to extract the most important components and dimensions of game-based education with emphasis on skills training in order to provide a comprehensive model as its main goal. The question is, what are the dimensions and elements of game-based education with emphasis on skill training?MethodThe present study is a qualitative study performed using metasynthesis method. In the present study, the use of metasynthesis method to identify elements related to the game-based education model with emphasis on skill training is such that researchers with a comprehensive and holistic view of the sources have done a thorough and in-depth review and related research findings combined to create comprehensive and interpretive findings. In order to achieve the purpose of the study, previous studies were reviewed and explored, and in this regard, the seven-step method of Barroso and Sandelowski (2007) was used.ResultsThe research was designed in the form of 8 dimensions and 19 components. The first dimension of a conceptual model is "motivation": the ability to achieve curriculum goals. The "individual" dimension includes: increasing self-confidence. The "skills": the ability to communicate effectively. The "cognitive": achieving mental development. The "learning" dimension includes: practical and experiential learning, the development of basic learning skills. "creativity": a platform for creating new ideas. The "physical": reduction of inactivity, physical growth and movment skills. The "therapy": expressing emotions. .DiscussionAccording to studies, cognitive processing of students is a very important issue; therefore, the results of the research in this dimension are consistent with the findings of Zeng et al. (2020) and Johann (2019). In terms of creativity and increasing creative thinking, it is consistent with the findings of Marcos et al. (2020) and in terms of physicality and energy depletion, which is accompanied by the development of movement skills, is also consistent with the findings of Chu, M. fowler (2020).